Online analysis for industrial bioprocesses: Broth analysis - Veloso, A. C. (2017)
This chapter will focus on the state of the art regarding analytical techniques used for the online assessment of key parameters in bioprocesses, such as biomass, substrate, product, and by-product levels during cell cultivation. It starts by presenting different monitoring approaches including in situ probes and automated at-line systems. It then reviews spectroscopic and mass spectrometry-based methods. Throughout the chapter, alternative techniques such as photometric sensors and calorespirometric methods, nuclear magnetic resonance spectroscopy, and biosensors are covered. A discussion on developments in software sensors is included.